Wawancan in the Traditional Wedding Ceremony of Lampung Sai Batin an Approach to Da'wah in Socio Cultural Context - M. Ibnu Naufal Maskuri; Fariza Makmun; Siti Wuryan; Umi Rojiati (LP2M UIN Sunan Kalijaga, 2026)
Abstract This study aims to examine the role of wawancan as a medium of dakwah in the Lampung Sai Batin wedding ritual, as well as how wawancan functions in the social and cultural context of the Lampung community. Wawancan, as a form of oral communication delivered by adat leaders or religious figures, not only serves to provide customary advice but also acts as a medium to convey Islamic dakwah messages. Using a qualitative approach with participatory observation and in-depth interviews, this research reveals how wawancan delivers religious and cultural values to the bride and groom as well as the attendees of the ceremony. The findings show that wawancan plays a significant role in uniting religious teachings and Lampung Sai Batin customs. As a dakwah medium, wawancan not only emphasizes religious messages but also strengthens social bonds within the community. Through wawancan, Islamic teachings are conveyed in a manner that aligns with local cultural values, making them easier to accept and understand. This study contributes to the understanding of how dakwah can be carried out by utilizing local cultural traditions, as well as the importance of preserving cultural heritage in the context of social and religious development in the Lampung community.